The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4322/rca.2012.009
|View full text |Cite
|
Sign up to set email alerts
|

Predição da precocidade sexual em bovinos da raça Nelore por meio de componentes principais

Abstract: Visual scores for precocity Visual scores for terminal carcass Predição da precocidade sexual em bovinos da raça Nelore por meio de componentes principais Prediction of sexual precocity in Nellore heifers using principal component analysis RESUMO: A eficiência reprodutiva e melhoria no desenvolvimento ponderal são as principais metas na pecuária de corte. O objetivo deste trabalho foi selecionar novilhas sexualmente mais precoces por meio de escores visuais de carcaça, peso e musculosidade. Dados de 283 fêmeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…Acta Scientiarum. Animal Sciences, v. 44, e53847, 2022 Other studies working with Nellore matrices (Semmelmann, Lobato, & Rocha, 2001;Freitas et al, 2011) have also reported positive association between weight at the beginning of reproduction and likelihood of pregnancy in heifers mated between 15 and 18 months, and heifers with greater weight at the beginning of the breeding season had better chances of becoming pregnant.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Acta Scientiarum. Animal Sciences, v. 44, e53847, 2022 Other studies working with Nellore matrices (Semmelmann, Lobato, & Rocha, 2001;Freitas et al, 2011) have also reported positive association between weight at the beginning of reproduction and likelihood of pregnancy in heifers mated between 15 and 18 months, and heifers with greater weight at the beginning of the breeding season had better chances of becoming pregnant.…”
Section: Resultsmentioning
confidence: 97%
“…One of the main causes of low economic results of cattle farming systems in tropical regions is due to the advanced age at first calving (AFC) in Zebu heifers (Freitas, Souza, & Moreira, 2011). Thus, the selection of matrices able to start breeding early is one of the requirements for increasing the profitability of the cattle, as it allows the production of an extra calf throughout its lifetime productivity.…”
Section: Introductionmentioning
confidence: 99%
“…A falha na reprodução é um dos mais importantes fatores que limita o desempenho da pecuária de corte brasileira. O baixo índice de desfrute do rebanho brasileiro, nos últimos anos, é resultado principalmente da elevada idade no que se refere ao primeiro parto e à baixa taxa de gestação das matrizes (FREITAS et al, 2011).…”
Section: Introductionunclassified
“…Dependendo das características envolvidas na avaliação genética e da estrutura dos dados, diferentes modelos são utilizados para a predição dos valores genéticos dos indivíduos (MARTINS et al, 1997). Henderson (1963) (MORRISON, 1976;MEYER e KIRKPATRICK, 2004;MEYER, 2005;YAMAKI et al, 2009;FREITAS, et al, 2011).…”
Section: Métodos De Predição Genéticaunclassified